Pengaruh Strategi Operasional, Manajemen Resiko Terhadap Strategi Pemasaran Serta Dampaknya Terhadap Kinerja Operasional Pada Sektor UKM di Kabupaten Serang - Yudi Guntara; Nita Anatriani (Cantaka: Jurnal Ilmu Ekonomi dan Manajemen, 2026)
This study aims to analyze the influence of operational strategy and risk management on marketing strategy and their impact on the operational performance of Small and Medium Enterprises (SMEs) in Serang Regency. The study is motivated by increasingly intense business competition, changing consumer behavior, and the growing complexity of business risks, which require SMEs to implement effective operational strategies and robust risk management systems to enhance their competitiveness. This research employs a quantitative approach using a survey method involving SME owners and managers in Serang Regency. Primary data were collected through questionnaire distribution and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) to examine the relationships among the variables. The findings indicate that both operational strategy and risk management have a positive and significant effect on marketing strategy. Furthermore, marketing strategy has a positive effect on operational performance and serves as a mediating variable that strengthens the relationship between operational strategy, risk management, and operational performance. This study contributes empirical evidence on the importance of integrating operational strategy, risk management, and marketing strategy as a foundation for policy formulation and strategic decision-making to improve operational effectiveness, competitiveness, and business sustainability among SMEs in Serang Regency.